lnnovative techniques for immature permanent teeth treatment – Pulp revascularization - Silva, Nathália Alves da (2022)
The treatment of incomplete rizogenesis and pulp necrosis presents a great challenge for endodontic therapy, mainly due to the fragility of the root walls of these teeth. The main therapy chosen is pulp revascularization with the aim of replacing damaged structures, including dentin and root structures, as well as cells of the dentin-pulp complex with a tissue that allows the root formation to continue in thickness and size. These procedures have been shown to be capable of promoting continuous root development, thus increasing the thickness and strength of previously thin fracture-prone roots.  The objective of this study is to carry out a review of the literature on pulpal revascularization and the clinical importance in the treatment of teeth affected by pulpal necrosis and whose apical formation has not yet been completed. A survey was performed on the PubMed platform and included articles published between 2004 and 2020. Pulp revascularization may be considered a promising alternative as the treatment for teeth with incomplete rizogenesis and pulp necrosis, the blinds struggle with the traditional apicification process.